2021
DOI: 10.1186/s12887-021-02605-3
|View full text |Cite
|
Sign up to set email alerts
|

Growth and neurodevelopment in low birth weight versus normal birth weight infants from birth to 24 months, born in an obstetric emergency hospital in Haiti, a prospective cohort study

Abstract: Background Low birthweight (LBW) infants are at higher risk of mortality and morbidity (growth, chronic disease and neurological problems) during their life. Due to the high incidence of (pre-) eclampsia in Haiti, LBW infants are common. We assessed the anthropometric growth (weight and length) and neurodevelopmental delay in LBW and normal birthweight (NBW) infants born at an obstetric emergency hospital in Port au Prince, Haiti, between 2014 and 2017. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…The speed of weight gain decreases rapidly after 3 months and then grow rapidly up to 6 months of age. 19 In our study this could not be concluded because of a short follow up span of 3 months. In multiple logistic regression analysis (Table 4), MAS, RDS, shock, AOP and positive CRP were found to be the independent risk factors contributing to neonatal mortality, which are similar with other studies like in Patel et al from India and Lin et al study from China.…”
Section: Discussionmentioning
confidence: 61%
“…The speed of weight gain decreases rapidly after 3 months and then grow rapidly up to 6 months of age. 19 In our study this could not be concluded because of a short follow up span of 3 months. In multiple logistic regression analysis (Table 4), MAS, RDS, shock, AOP and positive CRP were found to be the independent risk factors contributing to neonatal mortality, which are similar with other studies like in Patel et al from India and Lin et al study from China.…”
Section: Discussionmentioning
confidence: 61%
“…Bayi berat lahir sangat rendah (BBLR) berisiko tinggi mengalami infeksi selama periode antenatal, prenatal, dan postnatal. Pencegahan, diagnosis yang tepat, dan pengobatan akan menurunkan angka morbiditas dan mortalitas yang tinggi terkait dengan sepsis pada bayi BBLR (Hilaire et al, 2021). Ada kebutuhan untuk meningkatkan pengetahuan tentang faktor risiko dan mengatasi penyimpangan dalam pengenalan dan perawatan Bayi BBLR.…”
Section: Pembahasanunclassified
“…In this regard, healthcare workers, i.e., nurses, have an essential role in encouraging mothers to initiate and accomplish breastfeeding [ 12 ]. Meanwhile, healthcare workers should frequently assess the LBW infants’ weight and record their weight gain because of the significant relationship between weight gain and subsequent health outcomes of LBW [ 17 , 18 ]. Moreover, healthcare workers should provide continued care and apply education programs to help average infant growth and development [ 17 ].…”
Section: Introductionmentioning
confidence: 99%